To Be Lean or Agile in Supermarket Retail Industry: A Case Study on Sainsburys - Xu, Xin (2006)
Today, business environment is turbulent and volatile, how effective the company can build up the partnership with their business partners is the key to be able to compete in the national and global market. The merits of lean and agile supply chain strategies have been much debated among practitioners and academics. While these strategies are often viewed as opposites, this research supports the view that they must not necessarily compete and can, in fact, be employed simultaneously through a so called "leagile" approach. Lean, agile, and leagile strategies are illustrated by modeling their respective applications at supermarket retail industry. Even though the emergence of agile paradigm had spurred a large stream of research by scholars, yet most of the research had been at the manufacturing level. Very few researches have gone beyond the manufacturing level to the larger supply chain level. And there are even fewer researches discussing about the combination of lean thinking and agile thinking in supply chain especially apply in supermarket retail industry. Based on the above statement, the purpose of this study is as follows: 1) To evaluate the definition and characteristics of Lean and Agile in supermarket retail industry. 2) To compare the difference of lean thinking and agile thinking in supermarket retail industry. 3) To explore the relationship of the lean thinking and the agile thinking in supermarket retail industry. 4) To prove the practicability of the findings in supermarket retail industry. Finally author gains some findings, list as below: Under virtual manufacturing factory model, 1. The floating decoupling point will be one of the key strategic variables in the future supermarket retail industry. 2. Of the virtual decoupling point pipeline schemes, league is the most straightforward to apply. 3. Lean thinking can be used at upstream with smoothed demand to minimize the stock to minimize waste, but at downstream, there is high fluctuation, agile thinking can be adopted to meet the demand of the market responsively and flexibly. 4. In the virtual pipeline, the closer to the end, the better adopt agile approach. Under virtual production line in warehouse model, the Pareto Principle approach can be adopted as a mixed model in supermarket warehouse environments.